Studi Keruangan Pertumbuhan Sektor Industri Kecil dan Menengah Kabupaten Bangkalan - Hasan, Fuad (Universitas Trunojoyo Madura, 2009)
Small and medium industries, although not supported by big capital, but more able to survive in times of crisis. The purpose of this research is to determine the potential growth at small and medium industries in the district Bangkalan that has the potential small and medium industries, especially in the sectors of food, beverages and tobacco. Also small and medium industries in Bangkalan District also experienced such a rapid growth. Convergence of the distribution sector small and medium industries in the District Bangkalan business sector is dominated by food, beverages and tobacco. These business sectors are in Sub district Arosbaya, Bangkalan, Blega, Burneh, Galis, Kamal, Klampis, Kokop, Konang, Kwanyar, Labang ,Socah dan Tanah Merah. While the business sector and wood products are in District Sepulu, Tanjung Bumi and Tragah. Last is the business sector, non-metallic minerals products are in Sub Geger and Modung. Growth of small and medium industries in the District zs influenced byfactorsofBangkalan capital, the location associated with the distance to economic centers and duration of effort. While the amount olabor does not have a significant effect on development of small and medium industries in the District ofBangkalan.Keywords: SMEs, Balassa index, Regression nalysis",